Struktur Modal dan Kinerja Perusahaan (Studi pada perusahaan yang terdaftar di Bursa Efek Indonesia periode 2011 s/d 2012) - Budiarso, Novi S (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2014)
Abstract This paper examine the impact of capital structure on firm performance, in Indonesian Stock Exchange. Firm performance are analyzed from the side of accounting indicators, in this research use liquidity. Because the optimal level of debt of the firm is limited by the liquidity of the assets and it depends on the average usage of the debt in the particular industry. In the other side liquidity  is  conventionally  seen  as  reflecting  investors’  degree  of  risk -aversion, The study collects  of listed firms in Indonesian Stock Exchanges during 2011 to 2012. The listed firms on sub sector trade, services and investment. Multiple Regression analysis approach was employed in carrying out this analysis. Specifically, determined the simultaneous relationships among the various variables. The results show that as partial total debt to asset significantly influences to company’s performance but long term debt to asset not significantly influences to company’s performance. Simultaneously, total debt to asset and  long term debt to asset influences company’s performance. This evidence is consistent with models of optimal capital structure and with the hypothesis that debt level changes release information about changes in firm value/performance.